Design a Data Acquisition System on Deflection Test Equipment - Teguh Prasetyo; Hakam Muzakki; M Nur Rajab Zainal A (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The purpose of performing a deflection test is to determine the behavior of the material when given load variations. Acquisition data is used to read deflection value. Data acquisition is the process of collecting signals derived from changes in physical behavior, in this case read deflection on material test. The sensor used to read the behavior of the material when subjected to load is strain gauge BF 350 AA sensor. Data is captured in real time. Based on testing using a data acquisition system, deflection data was obtained with the smallest difference being 0.032 mm and the largest difference being 1.511 mm. The deflection stress data with the smallest difference is 0.742 N/mm2 and the largest difference is 250.816 N/mm2. The best deflection strain data acquisition system error rate value is 1.46% and the worst is 2.99%. As for the error rate value of the deflection stress data acquisition system, the best is 1.41% and the worst is 2.98%. Based on the error rate value of the strain-stress produced by the data acquisition system, it can be said that the data acquisition system is designed quite well.